Genome-wide association study indicates novel associations of annexin A13 to secretory and GAS2L2 with mucous otitis media - Bizaki-Vallaskangas, Argyro; Rämö, Joel; Sliz, Eeva; Kivekäs, Ilkka; Willberg, Tytti; Saarentaus, Elmo; Toppila-Salmi, Sanna; Dietz, Aarno; Haapaniemi, Teppo; Hytönen, Vesa P.; Toivola, Sari; Palotie, Aarno; et al. (NATURE PORTFOLIO, 2025)
To evaluate the genetics of chronic nonsuppurative otitis media (OM). We performed a genome-wide association study of 429,599 individuals included in the FinnGen study using three different case definitions: combined chronic nonsuppurative OM (7034 cases) (included serous and mucous chronic OM), mucous chronic OM (5953 cases), and secretory chronic OM (1689 cases). Individuals without otitis media were used as controls (417,745 controls). We used immunohistochemistry (IHC) of the murine middle ear to evaluate the expression of annexin A13. Four loci were significantly associated (p < 1.7 x 10(-8)) with nonsuppurative OM. Three out of the four association signals included missense variants in genes that may play a role in otitis media pathobiology. According to our subtype-specific analyses, one novel locus, located near ANXA13, was associated with secretory OM. Three loci (near TNFRSF13B, GAS2L2, and TBX1) were associated with mucous OM. Immunohistochemistry of murine middle ear samples revealed annexin A13 expression at the apical pole of the Eustachian tube epithelium as well as variable intensity of the secretory cells of the glandular structure in proximity to the Eustachian tube. We demonstrated that secretory and mucous OM have distinct and shared genetic associations. The association of GAS2L2 with ciliary epithelium function and the pathogenesis of dysfunctional mucosa in mucous OM is suggested. The abundant expression of annexin A13 in the Eustachian tube epithelium, along with its role in apical transport for the binding and transfer of phospholipids, indicates the role of annexin A13 and phospholipids in Eustachian tube dysfunction.